2001
DOI: 10.1074/jbc.m100768200
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Ku Antigen to Homeodomain Proteins Promotes Their Phosphorylation by DNA-dependent Protein Kinase

Abstract: The Ku antigen (70-and 80-kDa subunits) is a regulatory subunit of DNA-dependent protein kinase (DNA-PK) that promotes the recruitment of the catalytic subunit of DNA-PK (DNA-PK cs ) to DNA ends and to specific DNA sequences from which the kinase is activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 60 publications
(11 reference statements)
6
67
1
Order By: Relevance
“…As shown previously (Schild-Poulter et al, 2001), the phosphorylation of Oct-1 by DNA-PK was dependent on the interaction of Ku with the homeodomain. Thus, addition of a neutral HOXC4 homeodomain to the N-terminus of Oct-1 replaced the Oct-1 homeodomain in promoting strong phosphorylation of the peptide (Figure 2d).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…As shown previously (Schild-Poulter et al, 2001), the phosphorylation of Oct-1 by DNA-PK was dependent on the interaction of Ku with the homeodomain. Thus, addition of a neutral HOXC4 homeodomain to the N-terminus of Oct-1 replaced the Oct-1 homeodomain in promoting strong phosphorylation of the peptide (Figure 2d).…”
Section: Resultssupporting
confidence: 78%
“…By contrast, Oct-1 with substitutions in cluster D (Oct-1 D) was up-regulated to levels similar to the WT protein. This suggested that Oct-1 stabilization following IR treatment was mediated by the cumulative effects of residues phosphorylated in Oct-1 regions A, B and C. Importantly, the interaction between Oct-1 and Ku (Schild-Poulter et al, 2001 was not affected by the amino-acid substitutions in Oct-1 mtABC (Figure 3c). …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…DNA-PK and PARP1 have important functions in DNA double strand break repair, recombination, and telomere maintenance but are also involved in chromatin and transcriptional control 3638 . For example, Ku proteins associate with a series of homeodomain proteins (HOXC4, OCT1, OCT2, DLX2) thereby recruiting them to DNA ends where they are phosphorylated by DNA-PK 39 . Such phosphorylation was proposed to lead to DNA damage-dependent changes in their transcriptional activities.…”
Section: Resultsmentioning
confidence: 99%